Financial Management of Educational Operational Assistance in Improving the Quality of Education in Sesayap District, Tana Tidung Regency - Muhammad Noor Huda; Rahmat Hidayat; Titi Chandrawati (Program Pascasarjana Universitas Negeri Makassar, 2023)
Financial management of educational operational assistance (BOP) is school operational assistance originating from the Regional Government of Tana Tidung Regency which is used for school operational activities. The aims of this study are 1) to find out the financial management of educational operational assistance (BOP) to improve the quality of education in Sesayap District, Tana Tidung Regency; 2) to find out the inhibiting factors for operational assistance financial management (BOP) in Sesayap District, Tana Tidung Regency. The informants in this study were the Head of the Education Office, the Head of the Finance Subdivision of the Education Office, and the Principal of a school in Sesayap District, as well as one of the treasurers of the BOP. The research design used is qualitative with a case study approach. Data collection techniques used are interviews, observation, and documentation. The data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of the study show that 1) financial management of operational assistance (BOP) in improving the quality of education in Sesayap District, Tana Tidung Regency has been carried out in accordance with the provisions of 8 educational standards, namely graduate competency standards, content standards, process standards, assessment standards, educator and staff standards education, infrastructure standards, management standards, and financing standards analyzed from research indicators, namely fulfillment of financial obligations, honesty, control, responsibility, efficiency, and effectiveness; 2) the inhibiting factors in BOP financial management are delays in the disbursement of BOP from the district and the lack of awareness of financial responsibility from the organizers of activities or programs to the BOP treasurer of educational units.